2019
DOI: 10.1097/01.hs9.0000560524.63281.bc
|View full text |Cite
|
Sign up to set email alerts
|

Pf558 the Anti-Bcma Antibody-Drug Conjugate Gsk2857916 Drives Immunogenic Cell Death and Immune-Mediated Anti-Tumor Responses, and in Combination With an Ox40 Agonist Potentiates in Vivo Activity

Abstract: survival (OS) and progression free survival (PFS) in MM patients. Furthermore, the preclinical activity of a new GPRC5DxCD3 bispecific antibody (JNJ-7564) in development for the treatment of MM was evaluated, as well as biomarkers for in vitro JNJ-7564 response. Methods: GPRC5D protein expression was assessed by flow cytometry on BM MNCs derived from healthy donors (HD) and MM patients. GPRC5D gene expression levels were analyzed in purified CD138 + MM cells derived from patients who participated in 5 large ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…In preclinical in vitro and in vivo models, belamaf showed anti-MM activity without affecting BCMA-negative cells and the MMAF arrested the cell cycle of malignant plasma cells at the G2/M phase, eventually leading to cell death [88]. Its afucosylated Fc fraction promotes Fc-dependent immune effector functions, mainly ADCP and ADCC [89].…”
Section: Adcsmentioning
confidence: 99%
“…In preclinical in vitro and in vivo models, belamaf showed anti-MM activity without affecting BCMA-negative cells and the MMAF arrested the cell cycle of malignant plasma cells at the G2/M phase, eventually leading to cell death [88]. Its afucosylated Fc fraction promotes Fc-dependent immune effector functions, mainly ADCP and ADCC [89].…”
Section: Adcsmentioning
confidence: 99%
“…6,8,[10][11][12][13][14][15] Preclinical studies demonstrated encouraging anti-MM activity of belamaf through several mechanisms of action including direct apoptosis through the ADC mechanism, antibody-dependent cellular cytotoxicity, antibody-dependent cellular phagocytosis, and immunogenic cell death. 10,11,[14][15][16] Importantly, belamaf also demonstrated the ability to rapidly eliminate MM cells while sparing normal bone marrow stromal cells and immune effector cells when treated in co-culture. 10,11 Clinical data…”
Section: Preclinical Datamentioning
confidence: 99%
“…Belantamab mafodotin (GSK2857916) is an afucosylated, humanized IgG1 anti-B-cell maturation antigen (BCMA) mAb conjugated with monomethyl auristatin F (MMAF), which is a tubulin polymerization inhibitor [ 147 ]. Both parts (anti-BCMA antibody and MMAF toxin) are linked through a non-cleavable maleimidocaproyl linker, which provides better plasma stability of the compound without losing any property and without any nonspecific toxicity [ 148 ]. Belantamab mafodotin is the first anti-BCMA ADC approved by the FDA as a single agent for relapsed/refractory multiple myeloma (RRMM) patients who have received at least four prior therapies [ 149 ].…”
Section: Currently Approved Immunotherapeutic Treatments In MMmentioning
confidence: 99%
“…Belantamab mafodotin exerts its antimyeloma effect through four known mechanisms: (i) ADCC mediated by NK cells; (ii) recruitment of macrophages to promote ADCP; (iii) disruption of microtubules and subsequent G 2 /M cell-cycle arrest followed by apoptosis after the release of the MMAF toxin in the cytoplasm of myeloma cells [ 147 ] and (iv) induction of immunogenic cell death (ICD) [ 148 ], which is a mechanism characterized by the ability of dying cells to elicit robust adaptive immune responses against altered self-antigens or cancer-derived neo-epitopes [ 154 ]. In relation to the latter mechanism, preliminary data indicates that treatment of myeloma cells with belantamab mafodotin promotes the exposure of calreticulin (CALR) on their surface and the release of HMGB1, which subsequently induce the maturation and activation of DCs and eventually the activation of T cells [ 148 ].…”
Section: Currently Approved Immunotherapeutic Treatments In MMmentioning
confidence: 99%